Major cardiac surgery with recombinant FIX Fc fusion protein replacement in hemophilia B: a case report. (July 2022) - Bohn, Jan-Paul; Fiala, Anna; Bachmann, Sebastian; Irsara, Christian; Wolf, Dominik; Feistritzer, Clemens
The introduction of extended factor IX (FIX) products has significantly facilitated the treatment of hemophilia B patients. However, optimal perioperative management remains a topic of hot debate, particularly in surgeries with high bleeding risk. For the first time, we report here a patient with mild hemophilia B and degenerative aneurysms of aortic root and ascending aorta undergoing elective Bentall's operation with full cardiopulmonary bypass, who was successfully managed with eftrenonacog alfa (Alprolix ® ), a recombinant FIX Fc fusion protein (rFIXFc). rFIXFc could safely be monitored using the Pathromtin SL aPTT-reagent. No significant bleeding was noted intraoperatively despite systemic heparinization as well as postoperatively. Higher doses of rFIXFc were inevitable to reach target FIX levels intraoperatively, whereas in the post-surgery setting stable FIX concentrations were maintained with only few rFIXFc injections facilitating fast wound healing and remobilization of the patient.